Pergamon, Türkei. Die Altgrabungen auf dem Musalla Mezarlığı in Pergamon. Die Arbeiten des Jahres 2021 - Sliwka, Fabian (e-Forschungsberichte des DAI, 2021)
During a six-month DAI research grant from the Istanbul Department, the documentary material of the old excavations at Musalla Mezarlığı in ancient Pergamon, located in the Pergamon Archives, was newly recorded and examined with regard to its scientific informative value. From records already inserted into the iDAI.field database, an attempt was also made to obtain a quantitative overview of the excavations' excavated find material. The project served as preparation for a larger study possibly a dissertation, on the settlement and research history of the Musalla Mezarlığı and its find material. Due to the global pandemic, the project was worked on from home office.